Customer Expectation and Customer Satisfaction: Reviewing Service Quality of UBER - Valentine Siagian (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
This paper study the gap between the expected service and the reality of customer satisfaction from Uber’s customer perception. Service companies tend to be careful and pay more attention to the customers’ satisfaction and aim to have a good relationship to ensure their loyalty. Service quality dimension was used and applied to find the gap between customer expectation and customer satisfaction. The hypothesis was tested empirically to find how service quality (measured by five dimensions: tangibility, reliability, responsiveness, assurance and empathy) affects customer satisfaction on using Uber service. The result of F-test shows that service quality affect customer satisfaction positively. T-test shows that there is improvement needed on two dimension out of five. Star rating from Uber shows that customer satisfaction point is 4.6 out of 5, this paper shows that customer satisfaction result is 4.3 out of 5 from service quality dimension. Statistically this is a significant gap that needs to be filled to reach a closer gap to the expected service. Language barrier could be one of the reason to the gap that customer feels towards Uber driver. Including Taiwanese students as respondents could be done for further research